Refugee Rights and the Repatriation of Afghan Nationals: A Legal Perspective in Pakistan (PAKISTAN JOURNAL OF LAW, ANALYSIS AND WISDOM, 2024)
Pakistan, the state that crowds a substantial number of Afghan citizens, is in a predicament where the legal status of Afghan refugees living within its borders is unclear because the country has not formally ratified the 1951 Convention or its 1967 Protocol and has not passed any domestic legislation pertaining to the management of refugees. This article examines Pakistan's treatment of Afghan refugees in spite of the country's non-participation in the 1951 Refugee Convention and its 1967 Protocol, as well as the legal status of the refugees since their arrival in 1979. These people had difficulties because there was no national legislation that addressed refugee matters; instead, they were subject to the Foreigner's Act of 1946, which does not normally apply to them. This paper examines how the legal void has affected the lives of Afghan refugees, focusing on their arrival in Pakistan, changes in government policy, and the resulting legal complications. Pakistan has taken in Afghan refugees in spite of the lack of both international agreements and a national refugee statute. This has led to an analysis of the legal implications.